Effectiveness of weight loss program among young adults using diet and physical activity approach / Siti Sabariah Buhari ... [et al.] - Buhari, Siti Sabariah; Radzuan, Nuri Naqieyah; Abd Rahman, Nor Zafirah; Md Ahir, Nabilah; Ilias, Kartini; Md Yusof, Safiah (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Obesity among young adults has been a major concern in the health status of Malaysian populations. Increasing obesity rates among young adults in the Malaysian population need to be tackled using intervention programs involving behavioural approaches and delivered on an individual basis. This study aimed to assess the effectiveness of a weight loss program using a diet and physical activity approach among young adults. This study was conducted among young adults from a university in the Selangor region. Convenience sampling was used in recruiting the subjects. Subjects were overweight and obese young adults (BMI 25.0-39.0 kg/m2) and were grouped into a control group with no treatment and an intervention group which was supervised by certified trainers and dietitians along with the 12 weeks programs. To evaluate the dietary practice before the intervention, Multiple pass 24 hours diet recall was conducted among the groups. The short version of the International Physical Activity Questionnaire (IPAQ) was administered to assess the subject's physical activity level before the intervention program. This group was reassessed in the 8th and 12th weeks. This program was useful in reducing the percentage of body fat but not BMI and waist circumference. However, time and intervention effects show a large effect size on BMI respectively where the intervention group showed an -3.2% loss in BMI while the control group only showed -0.3% loss. The impact of strict intervention monitoring among subjects helped in the modification of behaviour changes across time. The study demonstrated the ability of intervention program through nutrition education and hands-on improving healthy eating, exercise, and weight among the subjects. This may help to improve the efficacy of behaviour changes among the obese population to continue their healthy lifestyle.